Psychological processes in the dynamics of reconciliation - Prieto Ursúa, María (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The aim of this paper is to define the psychological concepts of forgiveness and reconciliation and review the main differences between them, moving later to review the psychological aspects involved in reconciliation. To do this, the psychological processes of reconciliation proposed in different contexts (identity conflicts, couples in trouble, conflicts in the workplace, and divorced couples) are reviewed and the common factors are analyzed. Cognitive and behavioral processes are identified as common to all interventions, remaining the question about the role of emotional processes in reconciliation.